Propagação vegetativa de erva-baleeira (Varronia curassavica Jacq.) por estaquia - Sérgio Antônio Felix Júnior (2022)
Varronia curassavica Jacq. is a native medicinal species, with wide geographic dispersion and with anti-inflammatory properties. The cuttings can be used for multiplication of V. curassavica. Studies on the influence of cutting type and juvenility on adventitious rooting are scarce for this species. The objective was to analyze the feasibility of using semi-hardwood and woody cuttings for propagation by cuttings of Varronia curassavica Jacq. The survival, rooting, callogenesis and sprouting of semi-hardwood and woody cuttings were evaluated, when collected at different positions in the matrix plant, treated with indole butyric acid, as a function of shading levels and types of scarification at the base of the cutting. Two experiments were carried out, experiment I was carried out in a completely randomized design, 3x2 factorial scheme, the treatments are cutting position in the matrix plant and auxin application, four replications, 24 plots, and six cuttings per plot. The experiment II was carried out in a randomized block design, 3x3 factorial scheme, with plots divided into four blocks, with 36 plots and nine cuttings per plot. Levels of irradiance and types of scarification were evaluated. Assessments were performed 42 days after implantation. The variables analyzed were the percentage of live cuttings, with calluses and roots, number of roots, number of shoots, average root length, length of the largest root, fresh and dry root matter. The highest percentage of rooting and average length of the largest root were observed in basal cuttings (68.7% and 16.41 mm) and the highest percentage of cuttings with calluses and number of shoots were observed in cuttings with cross section (39, 8% and 0.30). Basal and intermediate woody cuttings are indicated for the vegetative propagation of V. curassavica, and the environment with greater irradiance provides better conditions for the development of cuttings and scarification at the base of the cutting did not increase adventitious rooting.